Confidence evaluation of fractures seismic detection in shale gas formations on WY23 Pad in Weirong - LI Jingchang, LU Ting, NIE Haikuan, FENG Dongjun, DU Wei, SUN Chuanxiang, LI Wangpeng (Youqicang pingjia yu kaifa)
Due to the inadequacy in the pre-assessment of natural fracture growth in shale, the exploration and development effect of Weirong shale gas field is seriously affected. It is imperative to enhance research on fracture prediction. In this paper, we applied the post-stack seismic dip-azimuth attribute to detect fractures in the WY23 Pad, and evaluated the reliability of the detection results from four aspects: geology, seismic, logging and engineering. The method employed for fracture detection revealed that fractures exhibit layer-controlled characteristics. They can be divided into two sets of upper and lower fracture systems roughly bounded by the top surface of the ③ thin layer. These fracture systems dip toward each other in the profile, with a predominant strike direction of 310° and dip angles of less than 20°. This configuration is the result of NE-SW compression. The application of this method for fracture detection has a high degree of confidence and can be promoted and applied in other development pad than WY23.